2019
DOI: 10.3390/microorganisms7110490
|View full text |Cite
|
Sign up to set email alerts
|

The Endophytic Fungus Chaetomium cupreum Regulates Expression of Genes Involved in the Tolerance to Metals and Plant Growth Promotion in Eucalyptus globulus Roots

Abstract: The endophytic strain Chaetomium cupreum isolated from metal-contaminated soil was inoculated in Eucalyptus globulus roots to identify genes involved in metal stress response and plant growth promotion. We analyzed the transcriptome of E. globulus roots inoculated with C. cupreum. De novo sequencing, assembly, and analysis were performed to identify molecular mechanisms involved in metal stress tolerance and plant growth promotion. A total of 393,371,743 paired-end reads were assembled into 135,155 putative tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 52 publications
(58 reference statements)
2
17
0
Order By: Relevance
“…The dual inoculation also affects the root exudates, which maybe directly related with improved plant growth [55]. In our study, malic and citric acids were observed as the main root exudates from plants under PAH stress, which agrees with recent studies analyzing the concentration of root exudates of native plants subjected to different abiotic stresses [79,80]. Furthermore, malic and citric acid can mobilize inorganic P in soil, promoting plant growth [81].…”
Section: Discussionsupporting
confidence: 90%
“…The dual inoculation also affects the root exudates, which maybe directly related with improved plant growth [55]. In our study, malic and citric acids were observed as the main root exudates from plants under PAH stress, which agrees with recent studies analyzing the concentration of root exudates of native plants subjected to different abiotic stresses [79,80]. Furthermore, malic and citric acid can mobilize inorganic P in soil, promoting plant growth [81].…”
Section: Discussionsupporting
confidence: 90%
“…It was found that Piriformospora indica, an endophytic fungus, promotes the growth of Arabidopsis and tobacco seedlings and enhances the expression of genes encoding nitrate reductase [51]. It was also noted that the endophytic fungus C. cupreum positively regulates the expression of some genes involved in auxin biosynthesis and metabolism in Eucalyptus globulus [52]. The modification of tomato root architecture is attributed to ethylene/indole-3-acetic acid signaling triggered by a strain of Trichoderma [53].…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that effective tolerance mechanisms can support colonization of acidic Andisols. One of the tolerance mechanisms can be related with speci c interactions with microbial strains which can confer metal tolerance to their associated plants (Ortiz et al, 2019). This is the case of Rhodococcus sp., which has been described as a microbial strain with high tolerance to metal(loid)s (Kumari et al, 2019;Vergani et al, 2019).…”
Section: Discussionmentioning
confidence: 99%